A Pilot, Community-Based Interventional Study in a Local Convenience Store to Improve Dietary Outcomes in Children - Foster, Byron A.; Reznik, Marina (International Journal of Child Health and Nutrition, 2013)
Introduction: One contributor to the epidemic of obesity is an unhealthful food environment. This study was designed to assess the feasibility of a community-level intervention in a convenience store on improving the food environment. Methods: This community-based interventional study took place in an urban, low-income, ethnic-minority neighborhood. Children who reported visiting either the intervention store or another neighborhood control store were enrolled. The healthfulness of store offerings was measured, and a diet survey was completed by subjects from both intervention and control stores. Results: At the nine-month follow-up, the intervention store promoted and advertised more healthful items than the community-control store. There was a trend toward increased fruit and vegetable consumption and lower sugar-sweetened soda consumption among the intervention store subjects but not in the control subjects. Conclusions: Improving the food environment is feasible via a community-based intervention utilizing the influence of a community health center.